Soft X‐ray Spectromicroscopic Investigation of Synthetic C‐S‐H and C3S Hydration Products. Issue 9 (19th June 2015) - Bae, Sungchul; Taylor, Rae; Hernández‐Cruz, Daniel; Yoon, Seyoon; Kilcoyne, David; Monteiro, Paulo J.M; Struble, L.
<x xml:space="preserve">Abstract</x> Calcium silicate hydrates (C‐S‐H), the primary binding phase in concrete, is the most prominent physiochemical factor controlling the mechanical and chemical properties in the production of concrete. This paper reports the local‐binding structure and morphological details of C‐S‐H as determined by high‐resolution X‐ray spectromicroscopy. Hydrated tricalcium silicate (C3S) was used to determine the properties and role of the outer products (Op) of C3S. C‐S‐H with different molar ratios of Ca/Si, were synthesized (Syn‐CSH) to quantitatively evaluate the effect of silicate polymerization on Ca L and Si K edge of C‐S‐H. Near edge X‐ray absorption fine structure (NEXAFS) spectroscopy of Syn‐CSH showed no variation in peak positions and energy separation for CaLIII, II edge for the Ca/Si ratios investigated. Compared to Syn‐CSH, C3S, when hydrated for 17 d, had a similar local structure around Ca. Si K edge NEXAFS analysis on Syn‐CSH showed a tendency for the peak positions of both the Si K edge and the peak induced by multiple scattering to shift to higher energy levels. The results also indicated that the distance between the two peaks increased with a decrease of the Ca/Si ratio in Syn‐CSH. Silicate polymerization influenced the multiple scattering of distant shell atoms more than the binding energy of the core atoms. Op of C3S had a uniform and higher degree of silicate polymerization compared to the core area. The results imply that Op reduces the hydration process of C3S into the core area thereby playing a key role on the properties of concrete upon formation.